Concomitant stress urinary incontinence and pelvic organ prolapse surgery: Opportunity or overtreatment?. (July 2020) - Pecchio, Silvia; Novara, Lorenzo; Sgro, Luca G.; Rapetti, Giulia; Fuso, Luca; Menato, Guido; Biglia, Nicoletta
Abstract: Objectives: The association between pelvic organ prolapse (POP) and stress urinary incontinence (SUI) is very common. When POP surgery is indicated and the patient has concomitant SUI, there are two treatment strategies: the one-step strategy (concomitant correction of POP and SUI) and the two-step strategy (correction of POP with subsequent evaluation of SUI). Guidelines from the International Continence Society and International Consultation on Incontinence recommend that a urodynamic assessment (UA) should be performed before surgery as this can reveal the presence of urodynamic SUI, but the role of UA is the subject of debate as it does not seem to improve treatment decisions. The aim of this study was to identify the presence of pre-operative urodynamic parameters that were predictive of POSUI, and to identify patients who could benefit from concomitant correction of SUI during POP surgery Study design: A retrospective evaluation was undertaken of 155 patients with at least second-degree POP who underwent POP surgery after UA between 2009 and 2016 in an Italian gynaecology and obstetrics department. Of these, 61 patients were clinically incontinent before surgery and 94 patients were clinically continent. After UA, patients were stratified using a maximum urethral closure pressure (MUCP) cut-off of 50 cmH2 O; the risk of POSUI was calculated using this value. Results: POP surgery alone resolved SUI in 60 % of the 61 clinically incontinent patients; only 30 % of these patients had urodynamic SUI and >50 % did not have POSUI. Thirty-six percent of the 94 continent patients had occult SUI on UA and 16 % developed de-novo POSUI. Seventy-five percent of all patients with occult SUI did not develop de-novo SUI. MUCP was lower in patients with POSUI than in patients without POSUI ( p =0.013). The probability of POSUI was higher in patients with MUCP ≤50 cmH2 O. The number needed to treat (NNT) to prevent one case of POSUI in these patients was 2, compared with an NNT of 4 in the continent group. Eight percent of patients underwent further surgery for SUI. Conclusions: Clinically incontinent patients with MUCP ≤50 cmH2 O will gain the greatest benefit from concomitant POP and SUI surgery. However, concomitant surgery has more severe adverse events. Given that 62.3 % of patients resolved SUI after POP surgery alone, it is important not to overtreat these women. Clinical pre-operative SUI is the best indicator of POSUI and was found to increase the risk of POSUI (odds ratio 3.2, 95 % confidence interval 1.5–6.8; p =0.003). Despite the small sample size, the two-step strategy appears to result in lower use of mid-urethral slings and a clear reduction in complications. It is important not to focus on the diagnosis of urodynamic SUI in continent patients but to evaluate MUCP carefully.